2023
DOI: 10.3390/plants12040746
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Phenolic Profiles of Achillea millefolium from Different Geographical Gradients

Abstract: The traditional widely used raw material of Achillea millefolium is currently mainly derived from wild populations, leading to diversification and uncertainty in its quality. The aim of the study was to determine the accumulation differences of phenolic compounds between geographically distant populations of Achillea millefolium from northern and southern gradients. Plant material was collected from Gaziantep and Nevşehir provinces in Turkey and from wild populations in Lithuania. A complex of nine hydroxycinn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Achillea spp. inflorescences were characterised by flavones as organ-specific compounds, while leaves were characterised by flavonols, especially rutin, which is in agreement with our previous studies [23,36]. Achillea spp.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Achillea spp. inflorescences were characterised by flavones as organ-specific compounds, while leaves were characterised by flavonols, especially rutin, which is in agreement with our previous studies [23,36]. Achillea spp.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have mainly focused on the characterisation of essential oils and flavonoid components of the typical white morphotype of A. millefolium in relation to external and internal cues [13,[23][24][25][26]. However, to date, no study has reported a detailed investigation of the triterpenoid profile in A. millefolium parts of the plant.…”
Section: Introductionmentioning
confidence: 99%
“…However, the concentration of phenolic compounds in T. vulgare depends on the type of habitat. The distribution of phenolic compounds in plants is difficult to explain by geographical differences in locations [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, one of the most famous plants from the genus Achillea is A. millefolium L., which is widely used in traditional medicine around the world and which undoubtedly has become a cosmopolitan species [12,13]. Phytochemical research has revealed that many compounds of this genus are very biologically active, and in particular, phenolics and flavonoids are the most important secondary metabolites, which have been proven to possess a wide range of pharmacological activities [14,15]. These activities mostly arise as a result of the synergistic effect of phenolics and flavonoids, as well as other groups of secondary metabolites that are present in plants of this genus.…”
Section: Introductionmentioning
confidence: 99%